Stock Price reaction to Cash dividend announcements in Viet Nam - Duong, Thi Minh Nguyet (H. : ĐHQGHN, 2020)
This study attempts to examine the reaction of stock prices to dividend announcements using data of Vietnam's listed companies at the Ho Chi Minh Stock Exchange (HOSE). This study employs event study methodology used in the sample 154 stocks that cash dividends were made in September 2018 to March 2O19.The investors consider dividend announcements as favorable news. The stock price reacts positively to subsequent dividend announcements. In fact, stocks include both dividend events increasing and decreasing. It also exists a situation for the cumulative abnormal return to go up in the pre-announcement but a downward trend after the post-announcement date. More specifically, I find that positive cumulative abrionpai returns around 0.0288% on the first day after the post-announcement.